2012
DOI: 10.1186/1471-2458-12-295
|View full text |Cite
|
Sign up to set email alerts
|

“Childhood overweight and obesity: maternal perceptions of the time for engaging in child weight management”

Abstract: BackgroundThere is an increasing awareness of the impact of parental risk perception on the weight course of the child and the parent’s readiness to engage in preventive efforts, but only less is known about factors related to the parental perception of the right time for the implementation of preventive activities. The aim of this study was to examine parental perceptions of the appropriate time to engage in child weight management strategies, and the factors associated with different weight points at which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 32 publications
6
38
1
5
Order By: Relevance
“…While this apparent lack of motivation may seem surprising, others have clearly shown that parents are not concerned about excess weight in young children until it really starts to impede their mental or physical health (4) . The dichotomy between parental ratings of the BMI values that suggest intervention is required, and that of expert committees, has been demonstrated previously (24,25) . Over 70 % of parents reported that the 90th BMI percentile is the minimum point at which weight management should be initiated, of whom one in five indicated that intervention should not happen until above the 97th percentile (24) .…”
Section: Discussionmentioning
confidence: 96%
“…While this apparent lack of motivation may seem surprising, others have clearly shown that parents are not concerned about excess weight in young children until it really starts to impede their mental or physical health (4) . The dichotomy between parental ratings of the BMI values that suggest intervention is required, and that of expert committees, has been demonstrated previously (24,25) . Over 70 % of parents reported that the 90th BMI percentile is the minimum point at which weight management should be initiated, of whom one in five indicated that intervention should not happen until above the 97th percentile (24) .…”
Section: Discussionmentioning
confidence: 96%
“…27,28 A German study evaluated the maternal perception of the child's silhouette and showed that some of the mothers of younger children preferred the child to be with overweight silhouettes. 29 In the cases of school types, it was verified that in public schools the mean overestimation was approximately five times bigger than in private ones, even though the highest difference has been only a little over 20 grams. This finding might be related to the more elevated frequencies of adolescents of lower socioeconomic classes in public schools and of mothers with a low level of education.…”
Section: Discussionmentioning
confidence: 90%
“…Há implicações do papel da família na obesidade das crianças e, mais especificamente, do papel das mães 4,7,8 . O reconhecimento do excesso de peso das crianças pode ser o requisito necessário para a procura de ajuda profissional e promover uma melhora na adesão ao tratamento, mas a percepção familiar distorcida faz com que o excesso de peso seja percebido como normal e desejável, impossibilitando tal ajuda [8][9][10] .…”
Section: Introductionunclassified
“…Um estudo alemão que avaliou a percepção materna em relação à silhueta do seu filho mostrou que parte das mães de crianças mais novas preferiam que o filho fosse mais gordinho 10 . Outro estudo de percepção, norte-americano, apontou que parte dos pais não estava preocupada com o peso dos filhos e subestimou este dado 11 .…”
Section: Introductionunclassified